Conception of final qualifying work in out-of-school educational establishment as the factor of forming of personalities qualities of man of informative society (Pedagogy of Higher and Secondary Education, 2007)
The article is devoted to determination of role of qualifying final work in out-of-school educational establishment as mechanism of socialization of child that the acquisitions to them the personalities socially claimed qualities. On the basis of connection of results of achievements of researches in area of pedagogical psychologists, pedagogic and sociology, an author determines the educational and educating aims of teacher in the process of organization of student at writing of final work.
Keywords: pedagogical purposes; information technologies; public consciousness; system